Systematic determination of TCR-antigen and peptide-MHC binding kinetics among field variants of a Theileria parva polymorphic CTL epitope - Svitek, Nicholas; Saya, Rosemary; Houshuang Zhang; Nene, Vishvanath M.; Steinaa, Lucilla (Oxford University Press, 2022)
CTLs are known to contribute to immunity toward Theileria parva, the causative agent of East Coast fever. The Tp967-75 CTL epitope from the Muguga strain of T. parva is polymorphic in other parasite strains. Identifying the amino acids important for MHC class I binding, as well as TCR recognition of epitopes, can allow the strategic selection of Ags to induce cellular immunity toward T. parva In this study, we characterized the amino acids important for MHC class I binding and TCR recognition in the Tp967-75 epitope using alanine scanning and a series of variant peptide sequences to probe these interactions. In a peptide-MHC class I binding assay, we found that the amino acids at positions 1, 2, and 3 were critical for binding to its restricting MHC class I molecule BoLA-1*023:01. With IFN-γ ELISPOT and peptide-MHC class I Tet staining assays on two parasite-specific bovine CTL lines, we showed that amino acids at positions 5-8 in the epitope were required for TCR recognition. Only two of eight naturally occurring polymorphic Tp9 epitopes were recognized by both CTLs. Finally, using a TCR avidity assay, we found that a higher TCR avidity was associated with a stronger functional response toward one of two variants recognized by the CTL. These data add to the growing knowledge on the cross-reactivity of epitope-specific CTLs and specificities that may be required in the selection of Ags in the design of a wide-spectrum vaccine for East Coast fever.